The Implementation of Wordwall Game to Improve Students’ Vocabulary Mastery - Mayaratih, Devy Aprilia; Permanasari, Pradnya (IKIP Siliwangi, 2025)
Vocabulary is one of the essential components in mastering English, yet many students find it difficult and boring to learn, especially when taught using traditional methods. This study examines the Wordwall Game as an interactive media to improve students' vocabulary mastery, particularly the simple past tense. This research utilizes a Classroom Action Research (CAR) design and involves 25 tenth-grade students of SMK Negeri 1 Kandeman. Two research cycles were conducted: planning, acting, observing, and reflecting. The researchers collected data using vocabulary tests (pre-test and post-test), observation checklists, and a student questionnaire. The findings show a significant improvement in students' vocabulary mastery, as reflected by the higher average score from 44.28 during the pre-test to 93.68 in the post-test cycle 2. The students also showed high motivation and enjoyment in using Wordwall. The interactive features of the game helped increase participation, reduce boredom, and make vocabulary practice more effective. It can be concluded that the Wordwall Game is an effective and fun learning tool to improve vocabulary mastery among vocational high school students.